Pengaruh Corporate Governance Terhadap Kualitas Sustainability Reporting - Christina Wishanarko Ekaputri; Rizky Eriandani (Universitas Serang Raya, 2022)
The sustainability report is an important part of the company's performance assessment. This study was conducted to fulfill a study on the influence of corporate governance on the quality of sustainability reports with a sustainability report index using a six point scale which was motivated by differences in thinking from previous researchers. This study uses a multiple linear regression model that will be carried out on 232 non-financial companies listed on the Indonesia Stock Exchange. Determination of the sample in the study using purposive sampling method and one shot method in obtaining data. The results of this study provide conclusions, namely: the results of the negative and significant effect of the proportion of independent commissioners on the quality of sustainability reporting, the results of no effect of the training of the board of commissioners on the quality of sustainability reporting, and the results of the negative and significant influence of the experience of the board of commissioners on the quality of sustainability reporting.